Effect of supported sitting position during second stage of labor on its outcome in primigravidae: A quasi-experimental study - Jagriti Chauhan; Himanshu Vyas; Pratibha Singh; Mukesh C. Sharma; Deviga Thirunavukkarasu (Journal of Family Medicine and Primary Care)
Background: The childbirth position has a significant influence on labor, maternal comfort, and neonatal outcome. In sitting position, there is a faster fetal descent with the effect of gravity. The information on this subject is relatively scant. Therefore, this study aimed to examine the effect of a supported sitting position during second stage of labor on its outcome in primigravidae. Materials and Methods: A quasi-experimental study with a post-test only control group design was used. 60 primigravidae were selected using total enumerative sampling. The labor outcome was assessed by self-structured maternal neonatal outcome checklist and socio-demographic proforma. Results: Statistically significant difference was observed on the mean duration of second stage of labor among primigravidae in control and experimental group (t = 5.87, P < 0.001) and also in the APGAR score of newborns (t = -3.98, P < 0.001). A statistical significant association of duration of second stage of labor with height and intensity of maternal work was also observed. Conclusions: A supported sitting position during labor was found to be effective in reducing duration of the second stage of labor. This can be used as a nursing intervention while providing care during labor especially at primary healthcare centers that can help in reducing the duration of second stage of labor.